Food resource matching by foraging tits Parus spp. during spring-summer in a Mediterranean mixed forest; evidence for an ideal free distribution - Díaz, Mario; ILLERA, JUAN CARLOS; ATIENZA, JUAN CARLOS (Ibis, 1998)
We analysed whether patterns of microhabitat use by Blue Tits Parus caeruleus, Great Tits Parus major and Crested Tits Parus cristatus inhabiting a mixed forest consistently matched the patterns of food availability experienced by foraging birds during spring-summer. The use of five microhabitats by each bird species (the foliage of three tree species, shrubs and ground) and the availability of food in trees during the prebreeding, breeding and post-breeding periods of the birds' annual cycle were measured. All three tit species foraged mainly in the outer part of tree canopies (small branches and leaves or needles). Tit distributions between tree species matched food resource distributions irrespective of overall food resource levels, which varied four-fold between the study periods, and tit species. Tits also exploited secondary microhabitats (shrubs and ground) in periods of low food availability; Blue Tits tended to use shrubs, whereas Great and Crested Tits foraged on the ground. Between-trees distributions fitted that expected from an ideal free distribution, suggesting that food availability and intraspecific exploitative competition were the main factors governing tree use by tits. In contrast, patterns of use of secondary microhabitats (shrubs and ground) seemed to indicate a role for the species-specific morphological configurations of each tit species since Blue Tits are better adapted to hang and tended to forage in shubs, whereas Great and Crested Tits are better adapted to feed on horizontal surfaces and tended to forage on the ground. No evidence of interspecific interactions was observed. Overall, the results pointed to an independent exploitation of Mediterranean mixed forest by each bird species, food availability and food accessibility being the main factors affecting microhabitat use by foraging tits.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: food availability; Foraging (voyant); microhabitat use; tits; Tree species

Food resource matching by foraging tits Parus spp. during spring-summer in a Mediterranean mixed forest; evidence for an ideal free distribution - Díaz, Mario; ILLERA, JUAN CARLOS; ATIENZA, JUAN CARLOS (Ibis, 1998)
We analysed whether patterns of microhabitat use by Blue Tits Parus caeruleus, Great Tits Parus major and Crested Tits Parus cristatus inhabiting a mixed forest consistently matched the patterns of food availability experienced by foraging birds during spring-summer. The use of five microhabitats by each bird species (the foliage of three tree species, shrubs and ground) and the availability of food in trees during the prebreeding, breeding and post-breeding periods of the birds' annual cycle were measured. All three tit species foraged mainly in the outer part of tree canopies (small branches and leaves or needles). Tit distributions between tree species matched food resource distributions irrespective of overall food resource levels, which varied four-fold between the study periods, and tit species. Tits also exploited secondary microhabitats (shrubs and ground) in periods of low food availability; Blue Tits tended to use shrubs, whereas Great and Crested Tits foraged on the ground. Between-trees distributions fitted that expected from an ideal free distribution, suggesting that food availability and intraspecific exploitative competition were the main factors governing tree use by tits. In contrast, patterns of use of secondary microhabitats (shrubs and ground) seemed to indicate a role for the species-specific morphological configurations of each tit species since Blue Tits are better adapted to hang and tended to forage in shubs, whereas Great and Crested Tits are better adapted to feed on horizontal surfaces and tended to forage on the ground. No evidence of interspecific interactions was observed. Overall, the results pointed to an independent exploitation of Mediterranean mixed forest by each bird species, food availability and food accessibility being the main factors affecting microhabitat use by foraging tits.
Keywords: food availability; Foraging (voyant); microhabitat use; tits; Tree species